Analyzing English with Jennifer YouTube Channel for Developing Discord EFL Users’ Vocabulary - Shagita Septianty; Fuad Abdul Baqi; Yuli Rohmiyati (CV. Edujavare Publishing, 2026)
Vocabulary plays a crucial role in supporting speaking skills, yet Indonesian EFL Discord users often experience speaking difficulties due to limited vocabulary, hesitation, and lack of confidence in real-time communication. This research aims to analyze the use of the ‘English with Jennifer’ YouTube channel for vocabulary development, examine its contribution to speaking skills, and identify challenges faced by EFL Discord users in applying new vocabulary in communication. This study employed a descriptive qualitative design involving six Indonesian EFL Discord users selected through purposive sampling. The data were collected through observation and post-observation interviews on Discord. The findings revealed that the ‘English with Jennifer’ YouTube channel contributed positively to vocabulary development through clear explanations, contextual vocabulary presentation, pronunciation modeling, and communicative learning activities for participants. The acquired vocabulary supported users' speaking performance by improving fluency, lexical variety, pronunciation awareness, and communication confidence. The main challenges identified included lexical retrieval difficulties, limited productive vocabulary, pronunciation issues, and speaking anxiety. In conclusion, the integration of the ‘English with Jennifer’ YouTube channel provides an effective digital learning environment for developing vocabulary to support Discord EFL users’ speaking skills.